Evaluación de fertilidad de suelo con orientación ganadera en el departamento Norte de Santander - Nancy Rodriguez Colorado; Daniel Antonio Hernández Villamizar; Cesar Augusto Uron Castro (Mundo Fesc)
Introduction. The recognition of soil characteristics has an important connotation in livestock farming since tropical production systems are based on grazing, making the bioavailability of nutrients in the soil a primary requirement for obtaining products such as weight gain or milk production. The objective of this research is the characterization of soils used in livestock farming in the department of Norte de Santander. Methodology. 210 properties dedicated to livestock farming with an age of more than 5 years were selected, located in 6 municipalities located in warm, temperate and high zones of the department of Norte de Santander. The physical and chemical properties of the soils of the experimental units were evaluated at a depth of 0-20 cm, such as apparent density (g/cc), texture to the touch, volumetric humidity (%) pH, cation exchange capacity, major elements nitrogen, phosphorus, potassium, organic matter, exchangeable bases Ca, Mg, K. Results and discussion. High variability was evident within municipalities, which requires careful analysis of differences between municipalities. Significant differences were found in the characteristics studied between municipalities (P ≤ 0.05). Pamplona was the municipality with the highest clay content, which was evidenced by better physical qualities, such as water retention, balanced nutrient content, and low aluminum content. Tarra was the municipality with the lowest organic matter and most acidic soils, representing macro- and micronutrient deficiencies. Conclusions. This study is a pioneer in soil characterization for livestock farming in the Norte de Santander department, as a strategy for technical improvement and recognition of weaknesses and potential.